KEBUTUHAN MAHASISWA AKAN MATERI AJAR MENULIS ARTIKEL DALAM BAHASA INGGRIS BERBASIS KRITERIA JURNAL-JURNAL BEREPUTASI - Mukhaiyar, Mukhaiyar; Syarif, Hermawati; Refnaldi, Refnaldi; Arianto, Muhammad Affandi (English Department FBS UNP, 2019)
Good teaching material can be defined as a material that is based on the results of needs analysis, so that it is not only about the significant effect on improving students' ability to write scientific articles but also the increasement of students’ knowledge and understanding on writing research articles. The purpose of this study was to analyze the level of students’ needs related to teaching material about how to write research articles based on the criteria of reputable journals. The research design used was survey research. Data was collected using a questionnaire related to the students’ needs toward teaching materials. The questionnaires were distributed to 120 students of English Language Teaching study programs who had learned article writing course. The results showed that the level of student needs regarding abstract and conclusion section are in the High category. Besides, the introduction, literature review, and methodological section are in the Very High category. From these findings, it can be concluded that the students' needs for teaching material related to English writing research articles based on the criteria of reputable journals is very high. Thus, teaching material writing research articles in English based on the criteria of reputable journals really needs to be developed.